Clinical utility and future direction of speaking valve: A review - Lian, Suna; Teng, Liying; Mao, Zhi; Jiang, Hongying (Frontiers in Surgery, 2022)
This paper summarizes and analyzes the clinical research progress of the speaking valve in recent years, including the structure and function of the speaking valve, the impact of the speaking valve on the patient’s vocalization or speech, the impact on ventilator weaning and tracheal intubation and extubation, and the effect on aspiration and swallowing function, the impact on patient mobility and quality of life. Related issues in clinical use are also described.